2016
DOI: 10.1136/bjsports-2016-096618
|View full text |Cite
|
Sign up to set email alerts
|

Pain, activities of daily living and sport function at different time points after hip arthroscopy in patients with femoroacetabular impingement: a systematic review with meta-analysis

Abstract: Aim To investigate pain, activities of daily living (ADL) function, sport function, quality of life and satisfaction at different time points after hip arthroscopy in patients with femoroacetabular impingement (FAI). Design Systematic review with meta-analysis. Weighted mean differences between preoperative and postoperative outcomes were calculated and used for meta-analysis. Data sources EMBASE, MEDLINE, SportsDiscus, CINAHL, Cochrane Library, and PEDro. Eligibility criteria for selecting studies Studies tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
85
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(93 citation statements)
references
References 56 publications
7
85
0
1
Order By: Relevance
“…A systematic review about pain, daily living activities, and returning after FAI surgery, found that the first clinically relevant improvement in hip pain was observed at 3 to 6 months after hip arthroscopy. Improvements in pain continued to postoperative 1 year [51]. Generally, we consider 1 year of follow-up, a sufficient time interval to predict if the patient could be a candidate for early revision surgery, including early conversion to THA.…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review about pain, daily living activities, and returning after FAI surgery, found that the first clinically relevant improvement in hip pain was observed at 3 to 6 months after hip arthroscopy. Improvements in pain continued to postoperative 1 year [51]. Generally, we consider 1 year of follow-up, a sufficient time interval to predict if the patient could be a candidate for early revision surgery, including early conversion to THA.…”
Section: Discussionmentioning
confidence: 99%
“…Trials are currently underway to compare surgical with conservative management and to investigate efficacy of postsurgical physiotherapy interventions for FAI syndrome and chondropathology (Bennell et al, ; Palmer et al, ; Kemp et al, ; Tijssen et al, ; Griffin et al, ). Surgery to correct the bony alignment and repair or resect the damaged acetabular labrum has been advocated, with good outcomes reported postoperatively (Kemp et al, ; Kierkegaard et al, ) although recent research has indicated that function and participation in sport and physical activity is still reduced 1 year after surgery (Thorborg et al, ). More recently, conservative nonsurgical management approaches focusing on improving neuromuscular function around the hip have been proposed as an alternative (Casartelli et al, ; Casartelli et al, ; Casartelli et al, ; Pennock et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Where sufficient data were available, sports activities were categorised using previously established criteria in which activities are grouped based on the mechanical load placed on the hip joint ( To accommodate heterogeneity in the reporting of duration of follow-up, data collection points were collated under the following time frames: ≤ 6 months, 7-12 months, 13-18 months, 19-24 months, ≥ 25 months. Improvements in activity-specific subscales are known to be limited beyond 2 years post-arthroscopy [11,35].…”
Section: Data Extraction Synthesis and Analysesmentioning
confidence: 99%
“…Despite this expectation, physical activity-related outcomes are only reported in approximately a quarter of studies investigating surgical intervention for FAIS [8], returning to sport or play being the predominant outcome assessed. A high level of return to sport/ return to play following hip arthroscopy (88-91%) has been reported in a number of systematic reviews [9][10][11][12][13][14][15][16] ; however, recent study findings suggest the need for a more expansive analysis, beyond these simplified nominal criteria, to assess the wider impact of hip arthroscopy on physical activity. When adding the further consideration of level to sports status, Ishøi et al [17] identified a relatively low return to pre-injury sport at pre-injury level of 57%, and Thorborg et al [18] identified that at 1 year post-arthroscopy, only 25% of patients that met physical activity reference scores commensurate with those expected in a healthy population.…”
Section: Introductionmentioning
confidence: 99%